Electrospun Antimicrobial Membranes-Functionality and Morphology - Nidal Hilal (Nanofiber Membranes for Medical, Environmental, and Energy Applications, 2019)
This chapter discusses the electrospinning process for the preparation of antimicrobial membranes. The recent acceleration in research into electrospinning has seen it emerge as a strong candidate for the commercial production of nanofibers for medical, filtration and textile applications. However, membrane fouling remains a significant barrier to the application of nanofibers to membrane processes. This chapter discusses the control of electrospinning parameters to modify nanofiber diameter and also addresses the role of nanofiber morphology on microbial adhesion; a major contributor to biofouling of nanofiber membranes. Inclusion of antimicrobials into nanofibers is explored with a focus on filtration applications.